2014
DOI: 10.1007/s10517-014-2536-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Female Sex Hormones on Adhesion of Candida Albicans Yeast-Like Fungi to the Buccal Epithelium

Abstract: Hormonal regulation of receptor expression and glycogen concentrations in the epithelial cells of the oral cavity remains poorly studied. Adhesion of microorganisms to the vaginal epithelium correlates with their adhesion to the buccal epithelium. Analysis of the correlation between Candida adhesion to the vaginal and buccal epithelium depending on the hormonal status has demonstrated that activity of Candida albicans strains in the buccal epithelium correlates with their adhesion activity in the vaginal epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Latimer et al [75] reported that these changes are mainly due to the response to stress conditions. However, they also argued that these changes are potentially the consequence of changes in the expression of the intercellular polysaccharides, protein PIA, and Aap, or rather changes in the staphylococcal accessory regulator gene sarA, which controls several virulence determinants, including biofilm formation, hemolysins, and DNase [75][76][77][78]. Although similar observations have not been made with the O-ECB, we strongly recommend the use of antimicrobials in general at bactericidal doses to limit possible adaptations.…”
Section: Toxicity Screen and In Vivo Antibacterial Activity Of Agnps ...mentioning
confidence: 85%
“…Latimer et al [75] reported that these changes are mainly due to the response to stress conditions. However, they also argued that these changes are potentially the consequence of changes in the expression of the intercellular polysaccharides, protein PIA, and Aap, or rather changes in the staphylococcal accessory regulator gene sarA, which controls several virulence determinants, including biofilm formation, hemolysins, and DNase [75][76][77][78]. Although similar observations have not been made with the O-ECB, we strongly recommend the use of antimicrobials in general at bactericidal doses to limit possible adaptations.…”
Section: Toxicity Screen and In Vivo Antibacterial Activity Of Agnps ...mentioning
confidence: 85%
“…The occurrence of genital candidiasis positively correlates with oestrogen levels, with oral contraceptives, hormone replacement treatment and pregnancy increasing the prevalence of Candida colonisation and vulvovaginal candidiasis (Spinillo et al, 1995;Bauters et al, 2002). Oestrogen levels have been implicated in regulating fungal morphogenesis and adhesion to the vaginal epithelium (Cheng et al, 2006;Kravtsov et al, 2014). However, the impact of oestrogen on the fungal cell wall has not been investigated.…”
Section: Environmental Impact On Cell Wall Carbohydratesmentioning
confidence: 99%
“…A number of researchers [37] have identified the influence of hormonal levels on the adhesiveness of the buccal epithelium in women during the menstrual cycle: the most active adhesion of candidal cells to epithelial cells was observed in the follicular phase of the cycle. This phenomenon, like the effect of corticosteroids, according to some scientists [38,39], may be associated with increased keratinization -keratinization of cells under the influence of estrogenic hormones.…”
Section: Main Partmentioning
confidence: 99%